(untitled) (Journal of Philosophy Culture and Political Science, 2023)
This article discusses the issue of the influence of distance education on the cultural layer of society at the present stage of development. The purpose of the article is to analyze development trends in the disclosure of the role of distance learning in modern cultural discourse at the global level, as well as in Kazakhstan. The scientific novelty of the study lies in the analysis of the specifics of modern distance learning from the point of view of cultural studies, as well as in clarifying the definition of "distance learning" in the context of cultural discourse. The field of education was one of the first to face global changes and the need for the development of distance technologies. In this regard, it is necessary to consider what the consequences and results of the educational process may be in a crisis. The study of changes in the education system in the context of a pandemic, conducting a comparative assessment are important from the point of view of further adaptation of the education system to crisis phenomena, the impact on the quality of education and the development of effective technologies for remote interaction of participants in the educational process. This article can be used as additional material for lectures and seminars on the discipline "Culturology". With the help of such methods as a comprehensive analysis of the essence and structure of the information component of modern culture, based on the application of an interdisciplinary approach; the principle of unity of the historical and logical, used in the analysis of trends in the development of the culture of the information society, the author comes to the conclusion that distance learning in cultural discourse considers the subject of learning uses time frames as the material foundations of a new culture that goes beyond the boundaries of a certain experience and includes a variety of representation systems , in which the boundaries between the real and the imaginary are mobile. Key words: enculturation, distance learning, cultural studies, culture, education, cultural paradigm.